2021
DOI: 10.1007/s11069-021-05030-y
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learnt from Typhoons Fitow and In-Fa: implications for improving urban flood resilience in Asian Coastal Cities

Abstract: Frequent typhoons are signi cantly affecting the coastal cities via intensive rainstorms, tidal surges and strong wind. Natural factors such as climate change and global sea-level rise come alongside anthropogenic factors such as rapid urbanisation and land use/land cover change leading to detrimental consequences such as urban oods. This short communication offers various lessons learnt by Ningbo municipality from two strong typhoons that hit the city directly, namely "Fitow" in 2013 and "In-Fa" in 2021. On t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Therefore, apart from traditional engineering measures, sufficient strategic planning and more flexible approaches are needed to enhance the resilience of the city [47]. For example, non-traditional approaches using big data and social media to improve the preparation and response of communities to floods have emerged recently [48,49]. These results are not only applicable in Hong Kong, but also of practical significance to other cities to enhance climate readiness, especially flood prevention and management.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, apart from traditional engineering measures, sufficient strategic planning and more flexible approaches are needed to enhance the resilience of the city [47]. For example, non-traditional approaches using big data and social media to improve the preparation and response of communities to floods have emerged recently [48,49]. These results are not only applicable in Hong Kong, but also of practical significance to other cities to enhance climate readiness, especially flood prevention and management.…”
Section: Discussionmentioning
confidence: 99%
“…Information technologies (e.g., news media, social media, 3D mapping services, Internet of Things) are encouraged to enhance better urban flood response during urban flood events. For example, using media data and technologies for better preparation and prevention noticeably reduced flood impacts in Ningbo during severe typhoon In-Fa event 2021 30 . Indeed, In-Fa caused a 150–200 mm/24 h rainstorm and severe surface water flooding in Ningbo, but successful preparation, response, and recovery ensured “zero causalities” and reduced substantial economic losses 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that social media is increasingly being used to respond to crises. Using big data and social media to improve flooding preparation and prevention significantly reduced flooding impacts (Chan et al, 2022). Social media is used for disaster preparation, response, mitigation and recovery (Tang et al, 2015;Carley et al, 2016;Cheng et al, 2019).…”
Section: Methodsmentioning
confidence: 99%